TRAINING SCHEMES AND TEACHERS’ ICT COMPETENCY DEVELOPMENT FOR INSTRUCTIONAL GOALS ATTAINMENT IN PRIVATE SECONDARY SCHOOLS IN RIVERS STATE (Journal of Association of Educational Management and Policy Practitioners, 2026)
The paper examined training schemes and teachers’ ICT competency development for instructional goals attainment in private secondary schools in Rivers State. It argued that targeted training schemes are essential for developing teachers’ ICT competency, which is a critical factor in achieving instructional goals. It contended that effective training programs should prioritize hands-on experience, coaching, self-directed learning, and ongoing-support through seminars and conferences to foster teachers’ confidence and pedagogical innovation. It reviewed existing literature on ICT tools and resources for effective instructional delivery, teachers’ ICT competences and indicators of teachers’ ICT competence. It examined the ICT competences required by teachers, and the professional development strategies for technology integration in education. More focus was then on the training schemes for teachers’ ICT competency development, and schemes such as ICT training workshops, coaching schemes, and self-directed learning schemes, among others were then thoroughly examined in the light of how they bring about teachers’ ICT competency development for instructional goals attainment in private secondary schools in Rivers State. The paper concluded that effective delivery of instruction in the 21st Century learning place is highly dependent on teacher’s ICT competences, which could be assured by regular training. The paper suggested among others that proprietors and proprietresses of private secondary schools in Rivers State should provide teachers with regular training opportunities, resources and support to develop their ICT competency.